Fungi yang Berasosiasi dengan Benih Acacia crassicarpa Sesaat Setelah Panen dan Setelah Penyimpanan - IGK Tapa Darma; Ari Sumrahadi (Institut Pertanian Bogor (IPB University), 2001)
Acacia crassicarpa is one of the forest tree species recommended for the establishment of Industrial Forest Plantations (Hutan Tanaman Industri/HTI) due to its fast growth on any soil type, and its prominent adaptability and resistance to sub-optimal field conditions, as well as to its high quality wood. One of the problems faced is the fact that the seeds are susceptible to pathogens soon after harvesting, as well as after they are stored. The pathogens cause seed-rot or reduce the germination percentage. The study was conducted to determine the storage fungi and their effects on the seed viability. The information gathered was expected to be useful for the development of the control method to reduce the loss due to fungal infection. In this study, 30 seed samples of A. crassicarpa were collected soon after harvesting and another 30 seed samples after 3-month placed in Dry Cold Storage. The germination and the infection percentages of the seeds were determined by employing the blotter test method (ISTA, 1976), 7 days after storage. The experiment was carried out in five replicates. Soon after harvesting, the fungal species associated with the seeds were Penicillium sp., Aspergillus sp., and Rhizopus sp.. Penicillium sp. was the dominant species with 40% seed infection and 73,3% seed germination. After 3-month placed in DCS, the same species were associated with the seeds and the dominant species was Rhizopus sp. with 77,3% seed infection and 60,7% seed germination.